Free-breathing dynamic liver examination using a radial 3D T1-weighted gradient echo sequence with moderate undersampling for patients with limited breath-holding capacity. Issue 86 (January 2017) - Kaltenbach, Benjamin; Roman, Andrei; Polkowski, Christoph; Gruber-Rouh, Tatjana; Bauer, Ralf W.; Hammerstingl, Renate; Vogl, Thomas J.; Zangos, Stephan
Highlights: Respiratory artifacts are a frequent problem in abdominal MR imaging. Non-diagnostic examinations could be reduced using free-breathing us-radial-VIBE for dynamic liver examination in challenging patients. Streak artifacts are characteristic for an undersampled radial acquisition but do not affect diagnostic validity. Abstract: Purpose: To compare free-breathing radial VIBE with moderate undersampling (us-radial-VIBE) with a standard breathhold T1-weighted volumetric interpolated sequence (3D GRE VIBE) in patients unable to suspend respiration during dynamic liver examination. Material and methods: 23 consecutive patients underwent dynamic liver MR examination using the free-breathing us-radial-VIBE sequence as part of their oncologic follow-up. All patients were eligible for the free-breathing protocol due to severe respiratory artifacts at the planning or precontrast sequences. The us-radial-VIBE acquisitions were compared to the patientś last staging liver MRI including a standard breathhold 3D GRE VIBE. For an objective image evaluation, signal intensity (SI), image noise (IN), signal-to-noise ratio (SNR) and contrast-enhancement ratio (CER) were compared. Representative image quality parameters, including typical artifacts were independently, retrospectively and blindly scored by four readers. Results: Us-radial-VIBE had significant lower SNR (p < 0.0001) and higher IN (p < 0.0001), whereas SI did not differ (p = 0.62). Temporal resolution assessed with CER in the arterial phase showed higher values for us-radial-VIBE (p = 0.028). Subjective image quality parameters received generally slightly higher scores for 3D GRE VIBE. In a smaller subgroup comprising patients with severe respiratory artifacts also at reference breathhold 3D GRE VIBE examination, us-radial-VIBE showed significantly higher image quality scores. Furthermore, there were generally more severe respiratory artifacts in 3D GRE VIBE, whereas streaking was characteristic in almost all us-radial-VIBE acquisitions but did not affect diagnostic validity. Conclusion: Free-breathing dynamic liver imaging using us-radial-VIBE delivers accurate temporal resolution, low motion artifact susceptibility and good image quality and represents a promising alternative in patients unable to suspend respiration.